The Urgency of Understanding Service Contractual Framework (Kafalah and Wakalah): A Fiqh Analysis Through Tafsir Al-Munir - Salsabilla, Dewi Insyirahti; Ali Muhtarom; Zawawi (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract Service-based contracts such as kafalah and wakalah play a significant role in contemporary Islamic financial transactions and business activities. However, their practical application often emphasizes contractual mechanisms that are not firmly grounded in normative foundations derived from the Qur'an and Hadith. This gap requires further understanding. This paper aims to analyze the urgency of understanding the contractual framework of kafalah and wakalah services through a fiqh-oriented interpretive lens, specifically the works of Wahbah Al-Zuhaili and relevant Prophetic traditions. This study employs a qualitative normative method using textual analysis of Qur'anic verses, classical and contemporary hadith and Wahbah Al-Zuhaili's fiqh-based approach complemented by contemporary Islamic legal literature on service contracts. The findings indicate that kafalah and wakalah are not merely technical legal instruments but embody ethical responsibility (Amanah) and social solidarity (Taawun), and trust as emphasized in the interpretation. Understanding kafalah and wakalah through the perspective of tafsir and hadith strengthens their ethical and jurisprudential dimensions for the application of contemporary Islamic economic practices and strengthens them in modern service-based transactions. Keywords: Akad; Contract; Business; Kafalah; Wakalah.   Abstrak Kontrak berbasis jasa seperti kafalah dan wakalah memainkan peran penting dalam transaksi keuangan dan aktivitas bisnis islam kontemporer. Namun, penerapan praktisnya seringkali menekankan mekanisme kontraktual belum kuat dalam landasan normatif yang berasal dari Al-Quran dan Al Hadis. Kesenjangan ini memerlukan pemahaman yang lebih. Jurnal ini bertujuan untuk menganalisis urgensi pemahaman kerangka kontraktual jasa kafalah dan wakalah melalui lensa interpretative berorientasi fiqh khususnya karya Wahbah Al-Zuhaili dan tradisi Nabi yang relevan. Penelitian ini menggunakan metode normative kualitatif dengan menggunakan analisis tekstual ayat-ayat Al-Qur;an, hadits klasik dan kontemporer dan pendekatan berbasis fiqh Wahbah Al Zuhaili dilengkapi dengan literatur hukum islam kontemporer tentang kontrak jasa. Hasil temuan menunjukkan bahwa kafalah dan wakalah bukan hanya instrument hukum teknis tetapi mewujudkan tanggung jawab etis (Amanah) dan solidaritas social (taawun), dan kepercayaan sebagaimana ditekankan dalam penafsiran. Memahami kafalah dan wakalah melalui perspektif tafsir dan hadis memperkuat dimensi etis dan yurisprudensialnya bagi penerapan praktik ekonomi islam kontemporer dan memperkuat dalam transaksi berbasis jasa modern. Kata Kunci: Akad; Jasa; Kafalah; Wakalah; Tafsir